TERMS DICTIONARY COMPUTER APPLICATIONS WITH MICROSOFT VISUAL BASIC 6.0 - Ibrahim Ibrahim; Erik Orlando, Skom, MMSI (Jurnal Sistem Informasi, 2005)
Every field of science has the terms in these disciplines, as well as a lot of computer science that there are terms in it, generally only those who learn the computer only understands these terms.To help find out the computer terms, the writer tries to make the Application Dictionary of Computer Terms with Visual Basic 6.0.Discussion of application of this dictionary is divided into four stages yaotu, making flowchart and algorithms, file structures, input and output design, and program development with Visual Basic 6.0.